The Effect of Yoga on Stress of Students: Exploring the Effects of Yoga on Stress Levels in Students (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Introduction Yoga is a science of right living and it works when integrated in our daily life. It works on allaspects of the person the physical, mental, emotional, psychic and spiritual. The word yoga means‘unity’ or ‘oneness’ and is derived from the Sanskrit word ‘yuj’ which means ‘to join’. Yoga through itstechniques of meditation, asanas, and pranayama yields a positive effect in the management of stress inadolescents. The processing of sensory information at the thalamic level is facilitated during the practiceof pranayama and meditation.Material Using stress inventory for school students (SISS) by Seema Rani and Dr. BasantBahadur SinghMethodology This study was conducted to find the effect of yoga on stress of subjects with the agerange 14 to 18 years. For this 30 subjects were drawn from Intercollege ofIndore, (M.P.)by usingpurposive sampling. Pre and post data were collected before and after yoga (treatment) for 10weeksusing stress inventory for school students (SISS).The selected subjects that are yoga practice(experimental group) was subjected to a 10-weeks yogic asanasprogram. Standing Postures, BalancingPostures, Arm-Balancing Postures, Inverted Postures, Backward-Bending Postureswere used as anyogic practice.Result and Conclusion The data collected for the study was statistically analyzed by using‘t’ ratio at 0.05level of significance. The calculated value of t ratio (=2.5181) is greater than tabulated t0.05 (58) (=2.0017).The effectiveness of yoga program may be attributed to the reason that yoga program decreasethe level of stress of an individual, as by practicing the yoga the arousal level of the individual isregulated which in return help us to decrease the stress level. Hence it is concluded thatYoga decreasesthe stress of students and produces positive and majorpart to decrease stress of students.